Elements of the Educational Project (Journal of Parents and Teachers, 1995)
The elements of the educational project include the mission and vision, which define the objectives and purposes of the project; the curriculum, which establishes the teaching content and methodologies; and the evaluation, which measures the progress and impact of learning. In addition, the human, material and financial resources necessary for its implementation are considered. These elements work together to create an effective and coherent educational environment.
Keywords: mission; curriculum; evaluation; resources